Laparoscopic Rectopexy Operative Procedure for Complete Rectal Prolapse among Female patients (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Laparoscopic rectopexy is performed to repair the complete rectal prolapse.Objective: The aim of this study was to see the safety of laparoscopic mesh rectopexy in patients with complete rectal prolapse after doing a case series at a tertiary care hospital.Methodology: This was a case series carried out at Shaheed Suhrawardy Medical College Hospital, Dhaka and at a private clinic from January 2005 to December 2010 for a period of 5 years. All female patients presented with complete rectal prolapse were included in this study. Follow up and outcomes were measured after operation.Result: A total number of 6 female patients were operated due to complete rectal prolapse. The mean age (iSD) of the study population was 64.4(i4.615) years. The age range was 58 to 70 years. The mean (iSD) duration of operation was 127.oi25.150 minutes. Constipation was reported in 33.3% cases of patients and 66.7% patients were without any complications.Conclusion: Laparoscopic mesh rectopexy is a technically feasible and safety method for treatment of complete rectal prolapse.J Shaheed Suhrawardy Med Coll, 2014; 6(2):67-70